Investors Implementing the Client Protection Principles in Microfinance - Lahaye, Estelle; McKee, Katherine (Washington, DC: World Bank, 2012)
Client protection is a key tenet of microfinance. The client protection principles and the smart campaign are the heart of an industry-wide initiative aimed at safeguarding the interests of microfinance clients. The end goal is adoption of appropriate policies, practices, and products by retail providers. By endorsing the six principles and joining the campaign, providers commit to take practical steps to treat clients fairly and respectfully while avoiding practices that might harm them.